A Note on the Practical Application of the Recommendations Made in the Indian Forest Bulletin No. 141, Regarding the Forecasting of the Quality of Teak from the Soil and Site Characteristics - Gupta, Raghunath S. (Indian Forester, 1950)
No abstract